El Excentrico, 1971-10-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
October 5, 1971 [5 de octubre de 1971]. No volume or issue number. Cover has a photograph of Ranchera singer Rosita Felix, "La Sultana" in a charra outfit.